An Association Between Maternal Intimate Partner Physical Violence and a Loaded Firearm in the Home - Burrell, Tierra D. (Journal of interpersonal violence, 2021)
A loaded firearm in the home increases the risk of firearm-related mortality. Furthermore, firearms are often used in fatal cases of intimate partner physical violence (IPPV) during pregnancy and in the postpartum period. Young children are often caught in the crossfire. Although firearms are more prevalent in homes with IPPV compared with homes without IPPV, little is known about the relationship between a loaded firearm and maternal IPPV. The objective was to determine whether maternal IPPV in the context of additional psychosocial factors is associated with a loaded firearm in the home. We analyzed population-based survey data (2004-2011) from the Centers for Disease Control and Prevention (CDC) Pregnancy Risk Assessment Monitoring System (PRAMS) in eight states for which questions on firearms were included. Chi-square analysis of independence was used to determine differences between mothers reporting both IPPV and a loaded firearm to mothers reporting IPPV only or a loaded firearm only. Multivariable weighted logistic regression examined the association between IPPV and presence of a loaded firearm in the home (adjusting for sociodemographic and psychosocial factors). Of the 43,845 mothers in our sample, 5.3% mothers reported storing a loaded firearm in the home and 6.7% reported maternal IPPV. Among mothers reporting IPPV, 5% also reported a loaded firearm. When adjusting for sociodemographic characteristics only, maternal IPPV was significantly associated with storing a loaded firearm in the home (adjusted odds ratio [aOR] = 1.39; 95% confidence interval [CI] = [1.01, 1.91]). However, after additionally considering psychosocial factors, there was no longer a statistically significant association between maternal IPPV and storing a loaded firearm in the home (aOR = 1.31; 95% CI = [0.93, 1.84]). Contextual factors play an important role in understanding the complex relationship between maternal IPPV and the presence of a loaded firearm in the home, and maternal IPPV should be considered in efforts to promote firearm safety.